2017
DOI: 10.1016/j.vaccine.2017.02.035
|View full text |Cite
|
Sign up to set email alerts
|

A randomized study of fever prophylaxis and the immunogenicity of routine pediatric vaccinations

Abstract: Prophylactic antipyretics affect immune responses to vaccines; these effects vary depending on the vaccine, antipyretic agent, and time of administration. In infants, paracetamol may interfere with immune responses to pneumococcal antigens, and ibuprofen may reduce responses to pertussis and tetanus antigens. The use of antipyretics for fever prophylaxis during infant vaccination merits careful consideration. ClinicalTrials.gov identifier: NCT01392378https://clinicaltrials.gov/ct2/show/NCT01392378?term=NCT0139… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
1
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
0
26
1
2
Order By: Relevance
“…After a booster dose, lower GMTs persisted in the prophylactic paracetamol group for all Pn serotypes, diphtheria, and tetanus (563). The one study that investigated the effect of ibuprofen administration around the time of vaccination shows that GMTs to FHA and tetanus are diminished after primary administration but not after a booster dose, while responses to conjugated Pn vaccine are not affected (564). Further, a recent large study in elderly individuals showed that the intake of statins diminishes GMTs to TIV (565).…”
Section: Administration Factorsmentioning
confidence: 99%
“…After a booster dose, lower GMTs persisted in the prophylactic paracetamol group for all Pn serotypes, diphtheria, and tetanus (563). The one study that investigated the effect of ibuprofen administration around the time of vaccination shows that GMTs to FHA and tetanus are diminished after primary administration but not after a booster dose, while responses to conjugated Pn vaccine are not affected (564). Further, a recent large study in elderly individuals showed that the intake of statins diminishes GMTs to TIV (565).…”
Section: Administration Factorsmentioning
confidence: 99%
“…Most of the preventable AEFI reports were due to the potential interaction between the components of the vaccines or between the vaccines and concomitant medications administered to the patients. Previous studies have documented poor immunologic response to conjugated Pneumococcus vaccine following acetaminophen administration (Prymula et al, 2009; Falup-Pecurariu et al, 2017; Wysocki et al, 2017). We also reported one case of interaction between varicella, live-attenuated vaccine, and the glucocorticoid betamethasone, which may result in an inadequate immunological response to the live vaccine (Infectious Diseases and Immunization Committee, Canadian Paediatric Society, 2000; Liu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These effects were especially apparent when antipyretic prophylaxis was administered at the time of primary vaccination, while no differences were observed after the booster dose. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic administration of paracetamol also seemed to interfere with immune responses to the PCV13 in infants, while ibuprofen appeared to reduce responses to pertussis filamentous haemagglutinin (FHA) and tetanus antigens without impacting pneumococcal responses. 11 …”
Section: Introductionmentioning
confidence: 99%